Jenseits agonistischer Planungstheorien: Die „Normalität“ von Protesten und ihr Einfluss auf die Konfliktaustragung in der räumlichen Planung - Bertram, Grischa Frederik; Altrock, Uwe (Raumforschung und Raumordnung | Spatial Research and Planning, 2023)
Since the “communicative turn“ planning research has been intensively concerned with how conflicts should and are dealt with. Approaches of “agonistic“ planning theory contradict the normative premise of building consensus among planning participants. Rather, they want to make conflicting positions normatively fruitful for spatial development. At the same time, they emphasise a supposed duality of planning and protest, which is questioned in recent protest and movement theory. Building on a discussion of different approaches in planning and protest theory as well as an empirical analysis of planning-related protests in Germany, this paper shows that these protests are increasingly perceived as “normality“ by planning actors and that antagonistic participation remains culturally bounded despite increasing conflictuality and the supposed questioning of representative democracy. Protest action is part of differentiated “participation bundles“ that, depending on the situation, also include public participation, direct democratic referenda and lawsuits. Protesters usually pursue a reform-oriented agenda that does not require “taming“. However, the underlying conflicts often cannot be “resolved“ at all. Planners, on the other hand, may have rationalist and deliberative approaches at their disposal even within an agonistic planning environment, which they use situationally and strategically.
Keywords: Protest; Conflict; Participation; Communication; Agonism